“Everything seems unreal”: How adolescents cope with COVID-19 quarantine experience - Adler, Asta; Stančaitienė, Gintė; Grauslienė, Izabelė; Nasvytienė, Dalia; Skabeikytė, Gabrielė; Barkauskienė, Rasa (Psichologija, 2021)
Adolescents were a particularly vulnerable group at the time of the pandemic. Restrictions applied during quarantine brought a lot of stress and challenges for the youth. The aim of this study was to reveal how adolescents cope with challenges faced during the lockdown due to COVID-19. Twenty four 13–17-year-old adolescents participated in a qualitative study using semi-structured in-depth interviews via Zoom. Findings revealed seven themes related to youth coping behavior during lockdown: 1. withdrawal behavior, 2. focus on particular activities, 3. social support seeking within family and via the internet with friends, 4. expression of overwhelming emotions, 5. protest against quarantine restrictions, 6. attempts to maintain “active oneself”, 7. search for the personal meaning of the lockdown. Understanding the coping behaviors and helping adolescents reflect their mental states in stressful situations could be effective interventions in order to reduce the risk of future psychological problems.
Keywords: adolescence; quarantine; coping strategies